The SSDC contribution to the improvement of knowledge by means of 3D data projections of minor bodies. Issue 8 (15th October 2018) - Zinzi, Angelo; Ciarniello, Mauro; Della Corte, Vincenzo; Ivanovski, Stavro; Longobardo, Andrea; Migliorini, Alessandra; Capria, Maria Teresa; Palomba, Ernesto; Rotundi, Alessandra
Abstract: The latest developments of planetary exploration missions devoted to minor bodies required new solutions to correctly visualize and analyze data acquired over irregularly shaped bodies. ASI Space Science Data Center (SSDC – ASI, formerly ASDC – ASI Science Data Center) worked on this task since early 2013, when started developing the web tool MATISSE (Multi-purpose Advanced Tool for the Instruments of the Solar System Exploration) mainly focused on the Rosetta/ESA space mission data. In order to visualize very high-resolution shape models, MATISSE uses a Python module (vtpMaker), which can also be launched as a stand-alone command-line software. MATISSE and vtpMaker are part of the SSDC contribution to the new challenges imposed by the "orbital exploration" of minor bodies: (1) MATISSE allows to search for specific observations inside datasets and then analyze them in parallel, providing high-level outputs; (2) the 3D capabilities of both tools are critical in inferring information otherwise difficult to retrieve for non-spherical targets and, as in the case for the GIADA instrument onboard Rosetta, to visualize data related to the coma. New tasks and features adding valuable capabilities to the minor bodies SSDC tools are planned for the near future thanks to new collaborations.